Budaya dan Kebijakan Organisasi dalam Manajemen Stres Kerja: Sebuah Kajian Pustaka - Muhammad Fathur Rozaq; Mutiara Safitri; Fardi Rahmat Dinata (Education : Jurnal Sosial Humaniora dan Pendidikan, 2026)
Organizational stress is one of the problems frequently encountered in the work environment and can affect employee productivity and performance. Excessive workload, work conflicts, uncomfortable work environments, and organizational pressures are factors that trigger work stress. Therefore, organizations need to implement effective stress management to create a healthy and productive work atmosphere. Methods: This article uses a literature study method by reviewing several theories and references related to organization-based stress management. The discussion focuses on the understanding of stress management, factors causing stress in organizations, and strategies used to overcome work stress. Results: The study shows that organizational stress management can help reduce the negative impacts of stress through workload management, effective communication, leadership support, and the creation of a conducive work environment. Proper stress management also contributes to improving employee motivation, comfort, and productivity. Conclusion: Organizational-based stress management is important to implement in order to create a healthy, comfortable, and productive work environment. Effective stress management strategies can minimize the negative effects of work stress and support the achievement of organizational goals.